Aktualizacija učnih vsebin z vidika vrednot prostora in participacije javnosti v procesu prostorskega planiranja - Kušar, Simon (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2008)
Since education is a key element in achieving goals of sustainable (spatial) development and for successful public participation in the planning process, these topics should be incorporated into the formal educational system as well. The article presents topics discussing values of space and spatial planning with which selected curricula on the primary and secondary level of education were supplemented during their renewal in 2007.
Keywords: geografija; geography; prostor; Subdivisions of the Kingdom of Yugoslavia; pokrajina; prostorski razvoj; prostorsko planiranje; spatial planning; sonaravni razvoj; sustainable development; trajnostni razvoj; vrednote; education; izobraževanje; pouk; curriculum; kurikulum